Сравнение методов толщинометрии - Велентеенко, Р. Е. (ХНУРЕ, 2020)
In modern industry in the manufacturing processvery often used expensive materials, technologically sophisticated products, components access to some parts of which is limited. For these cases, thickness gauge is the most optimal control option, due to the fact that it does not require destruction controlled sample (with ultrasonic method) and provides for the possibility further operation of the facility after the necessary measurements. Modern technologies require manufacturing quality controlmaterials, its thickness and integrity. Produced product can becheck with a thickness gauge to confirm its claimedthickness characteristics, as well as the thickness of coatings. There are several methods for controlling the thickness of materials: - mechanical; - electromagnetic; - eddy current; - ultrasonic; - magnetic
Keywords: толщинометрия; ультразвуковой метод; механический метод; электромагнитный метод; вихретоковый метод; магнитный метод